Kenapa Wajib Pajak UMKM Enggan Membayar Pajak Penghasilan? - Sari, Ni Putu Rossica; Maradona, Agus Fredy (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p17, 2020)
To boost tax revenues from the SMEs sector, the government has reduced the income tax rate for SMEs through the issuance of PP Number 23 of 2018. Nevertheless, in some regions, the tax revenues from the SMEs sector have, unexpectedly, decreased. The purpose of this study is to investigate the reasons for the lack of compliance by SME taxpayers, using the theory of planned behaviour as a theoretical framework. This study employed an exploratory design using a qualitative approach, in which the service areas of the Singaraja tax office served as the research setting. The results of this study show that the primary determinant of SME taxpayers’ compliance in paying income tax is the taxpayers’ consciousness concerning the importance of tax revenues for the country’s financial wellbeing. This finding provides significant implications for the Indonesian tax authority concerning their mission to increase the compliance level of SMEs taxpayers in fulfilling their tax obligations. Keywords: Taxpayer Compliance; SME; PP Number 23 Of 2018; Taxpayer Awareness; Theory Of Planned Behaviour.